ANALISIS STRUKTUR MODAL & FAKTOR YANG MEMPENGARUHINYA PADA SUB SEKTOR PROPERTI & REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2011-2015 - Yuhelmi Yuhelmi (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2018)
This study aims to analyze the Capital Structure as well as factors that affect it on the company in Sub Sector Property & Real Estate listed on the Indonesia Stock Exchangeperiod 2011 to 2015. The sampling technique in this study is the technique of Full Samplingwhere all the population into a sample that is as many as 26 companies. The analytical method used to test the factors affecting the Capital Structure is Multiple Linear Regression and using t Test.This study found that profitability and asset structure has no significant effect on Capital Structure while firm size has positive effect on Capital Structure.